FEATURES OF ACCOUNTING AUTOMATION AT ENTERPRISES IN UZBEKISTAN - G.T. Akhmedova (PT. Antis International Publisher, 2024)
The article analyzes the problems of accounting automation at enterprises, discusses possible ways to solve this problem. The author's approach defines a set of actions and measures aimed at improving the quality of accounting and simplifying accounting at enterprises in Uzbekistan.